Penderitaan sebagai Jalan Mistik Menuju Kesatuan Hidup bersama Kristus: Belajar dari Perjalanan Paulus Ke Sorga (2 Korintus 12:1-10) - Firman Panjaitan (UIN Sunan Gunung Djati Bandung, 2021)
Suffering is the secret of human life. Generally, people view suffering as God's reaction to human sin. This view is corrected by Paul in 2 Corinthians 12: 1-10, which emphasizes that suffering is not God's punishment but God's way of maintaining human humility in facing life. By using the rhetorical critique method, which is a method that explores understanding by creating a single literary genre from many inter-textualities, both in biblical texts and extra-biblical texts, this researcher finds a message that suffering is actually a 'mystical path’ to experience encounter and union with God. In union with God, humans realize that they are part of life as a whole, so they must share and care for each other based on the understanding that all human beings are part of Divine life. Thus 2 Corinthians 12: 1-10 affirms that suffering is not a negative thing and needs to be complained about, but must be grateful for the understanding that this is the ‘mystical path’ of humans towards the unity of life with Christ and fellow humans.